(untitled) (The Journal of Sindhuli Multiple Campus, 2026)
Skill represents the ability to apply theoretical knowledge and understanding in practical situations. Number of management graduates (BBS, BBA, BBM, MBS, MBA) are increasing. However, there is persistent skills gap that limits workforce readiness, organizational efficiency, and economic growth. This study examines four critical skill dimensions relevant to management graduates: they are conceptual, technical, communication, and behavioural skills. Some of the theories are also reviewed. This article also analyzes the causes and effects of skill gaps by reviewing academic studies, government reports, and relevant theories on workforce skills and management education. It examines how factors like weaknesses in the education system, limited practical exposure, and weak industry–academia collaboration create skill deficiencies. And, discussion also has been done to bridge deficiencies in skills required by business entities. In methodological part, this article uses a qualitative, descriptive methodology. Secondary data from academic literature, government reports, and international organizations were collected. The collected data were analyzed and many weaknesses are identified. Many weaknesses are found; like structural weaknesses in Nepal’s management education, limited practical exposure, and insufficient industry-academia linkages, etc. Results of the article aim to imply that the skills gap is to be addressed with some reforms, collaboration, and training. Having co-operation such as curriculum reforms, as well as closer cooperation between business schools and organizations is highly significant. In the same manner, wider vocational and computer education, and tactical investment in the ongoing professional growth is the solution to the immediate correction.